2016
DOI: 10.1080/08997659.2015.1114534
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Strawberry Disease in Farmed Chilean Rainbow Trout

Abstract: Strawberry disease is a chronic, nonlethal skin condition that affects Rainbow Trout Oncorhynchus mykiss in the United States and several European countries, where it is also known as red-mark syndrome. We provide the first identification and characterization of three strawberry disease outbreaks occurring at two aquaculture farms in southern Chile. Clinically affected fish weighing an average of 400 g presented multiple bright-red, usually raised, skin lesions on the flank, ventral surface, and dorsal surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…The present case report on RMS in Slovenia, together with the recent demonstrations of RMS in Turkey (Kubilay et al., ), Iran (Sasani et al., ) and Chile (Sandoval et al., ), indicates that the disease is further expanding in Europe and other continents, emphasizing the need of appropriate control measures as well as the collection of epidemiological data.…”
Section: Results Of the Tem And Pcr Assays Performed On The Skin And supporting
confidence: 56%
See 1 more Smart Citation
“…The present case report on RMS in Slovenia, together with the recent demonstrations of RMS in Turkey (Kubilay et al., ), Iran (Sasani et al., ) and Chile (Sandoval et al., ), indicates that the disease is further expanding in Europe and other continents, emphasizing the need of appropriate control measures as well as the collection of epidemiological data.…”
Section: Results Of the Tem And Pcr Assays Performed On The Skin And supporting
confidence: 56%
“…Red mark syndrome (RMS) is an inflammatory skin disorder spreading in farmed adult rainbow trout ( Oncorhynchus mykiss ), firstly reported in the UK (Ferguson et al., ; Noguera, ; Oidtmann & Noguera, ; Verner‐Jeffreys et al., , ) and USA (LaPatra, Groff, Lauda, Munn, & Jones, ; Lloyd et al., ; Olson, Beleau, Busch, Roberts, & Krieger, ), then signalled in Finland (Bruno, Crumlish, LaPatra, Noguera, & Verner‐Jeffreys, ), Austria, Switzerland (Schmidt‐Posthaus, Bergmann, Knüsel, Heistinger, & Licek, ), Italy (Galeotti, Giavenni, Volpatti, Beraldo, & Feist, ), Turkey (Kubilay et al., ), Iran (Sasani, Shokrpoor, Rahmati‐Holasoo, & Zargar, ) and Chile (Sandoval et al., ). The disease classical signs have recently been well characterized according to the criteria of Oidtmann et al.…”
Section: Results Of the Tem And Pcr Assays Performed On The Skin And mentioning
confidence: 99%
“…Red mark syndrome (RMS) or cold water strawberry disease is a skin disease observed in farmed rainbow trout ( Oncorhynchus mykiss ). The disease was described for the first time in Scotland (Ferguson et al, ; Verner‐Jeffreys et al, , ) and was, thereafter, reported in various European countries (Ferguson et al, ; Fleury, Vuillaume, & Sochon, ; Galeotti, Ronza, et al, ), Turkey (Kubilay et al, ), Iran (Sasani, Shokrpoor, Rahmati‐Holasoo, & Zagar, ) and Chile (Sandoval et al, ). The disease is very similar to UK strawberry disease and might be regarded as the same (Metselaar et al, ; Oidtmann et al, ).…”
Section: Attributes Of Red Mark Syndrome (Rms) In Rainbow Trout As Dementioning
confidence: 99%
“…Flavobacteriosis was treated with florfenicol. Strawberry disease is thought to be caused by a Rickettsia ‐like organism (Lloyd et al, 2011; Sandoval et al, 2016; Christie et al, 2018) and typically occurs in adults weighing between 200 and 300 g. This disease was treated with florfenicol or oxytetracycline. Antibiotic doses were reported as milligrams of antibiotic per kilogram of fish treated or as grams of antibiotic used per biomass (ton of fish treated).…”
Section: Resultsmentioning
confidence: 99%